2009
DOI: 10.5012/bkcs.2009.30.12.3098
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vaccinia H1-related (VHR) Phosphatase Activity by NSC-87877

Abstract: Half maximal inhibitory constant of enzyme was determined to 7.83 ± 0.98 µM. VHR phosphatase (100 nM) was incubated with various concentrations of NSC-87877 at 37 o C for 30 min. Fluorescence emission from the product was measured with a multiwell plate reader as described in Experimental section.Based on amino-acid sequences of catalytic domains, protein tyrosine phosphatases (PTPs) can be classified into four groups 1 ; class I Cys-based PTPs, class II Cys-based PTPs, class III Cys-based PTPs, and Asp-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…[25][26][27][28][29] In this study, we confirmed that PRL-3 inhibitor I which regulates SHP-2 function could be a promising target for drug development.…”
supporting
confidence: 58%
“…[25][26][27][28][29] In this study, we confirmed that PRL-3 inhibitor I which regulates SHP-2 function could be a promising target for drug development.…”
supporting
confidence: 58%
“…12,13 Using in vitro phosphatase assays, we have previously found that DUSP3, DUSP14, DUSP23, DUSP26, ACP1, Cdc25A and Cdc25B are inhibited by NSC-87877. [14][15][16][17][18][19] PTPs that are inhibited by NSC-87877 and their specificity for MAPKs were listed in Table 1. Since those NSC-87877 targets are involved in either cell growth or apoptosis, it is of interest to investigate whether cells survive or die when cells are treated with NSC-87877.…”
mentioning
confidence: 99%